Quantitative and qualitative analysis of sunflower pollen (Helianthus L.) and it’s use in breeding work - O. N. Voronova; V. A. Gavrilova (Труды по прикладной ботанике, генетике и селекции)
Background. In breeding work, it is necessary to take into account such an important feature as male sterility of the hybrids obtained. If a plant has visually visible anthers and pollen, the quality of the pollen grains themselves may be low. It is necessary to carry out not only a visual analysis, but also a cytological study of pollen in order to properly assess the reproductive potential of plants.Materials and methods. Wild species, some cultivars, lines and hybrids of sunflower from the collection of the N. I. Vavilov All-Russian Institute of Plant Genetic Resources were taken as objects of research. The plants were grown on the fields of Kuban Experiment Station. Pollen was collected from preinsulated inflorescences, fixed in FAA solution and stained with acetocarmine. The ratio of fertile pollen grains to the total number of pollen grains (in %) was calculated, the diameter of the pollen grains was measured, and variability curves were drawn.Results. Mature pollen grains in sunflower are rounded, tricolpate-poral, threecelled; the average pollen diameter in cultivated sunflower is 28–32 μm; in wild species, the range is from 20– 22 μm to 32–34 μm. All accessions were divided into three groups. Fertile: high level of fertility (75–99%) and low morphological heterogeneity of pollen; the variation curve for the average diameter was characterized by one distinct peak. Most of the studied accessions were included here: cultivars, most of the lines and some of the wild species. Semi-fertile: the number of well-stained pollen grains is below 75%; there are differences in the degree of staining and size of the pollen; the variation curve had additional peaks. This group included some of the lines, hybrids and wild species. The greatest morphological heterogeneity was observed in the group of perennial interspecific hybrids. Sterile: pollen grains were absent or were observed very sporadically.Conclusion. To assess the fertility of plants, it is important not only to determine the degree of staining in pollen grains, but also to rank them by diameter and construct variation curves to reveal morphological heterogeneity of pollen.